Optimalisasi Peran Sekolah Inklusi - Reni Ariastuti; Vitri Dyah Herawati (Universitas Mathla'ul Anwar Banten, 2016)
Every Indonesian citizen has the right to get a decent education and teaching, not least for those children with special needs (ABK). SD Lazuardi Kamila may use as an information referral inclusive school in Surakarta, existence is capable of being a facilitator for the inclusion of other schools to further develop and improve themselves for educational purposes such inclusion can be more optimal. This IbM activity aims to: (1) the teacher can determine the level of need crews primarily on the healthcare, (2) the teacher can understand how to be a teacher-friendly (welcoming teacher) in the school inclusion, (3) the teacher can make early detection of the growth protege (4) teachers can design learning, and (5) the management of the school is to prepare the required facilitation of inclusive education. Referring to objectives, the method is performed in service activities are conducting trainings and workshops directly to the participant/teacher. This activity was followed with the assistance of the participants that this activity can be sustained. From this activity provides benefits to the community, particularly the development of soft skills training and a teacher of children with special needs with the birth of inclusive schools friendly to children. Tools educational games are also given to crew members in order to support the therapy and also their education.